A Review on the Historical Development of Phytoplankton in the Philippines and their Biological Importance throughout the Years - S, Hernando Alice Geraldine; Baldia, Susana F.; Jr., Paciente A. Cordero (Asian Journal of Biological and Life Sciences, 2020)
Microalgae or commonly known as phytoplankton are the earliest and oldest forms of life on this living planet and considered as tiniest plant in the archipelago. These organisms display different colorations in water such as green, blue-green and brown. At present, phytoplankton are gaining much attention for feed, food and other important products in various fields and industries yet they are thought of as the most poorly studied group of aquatic organisms. Noteworthy, some of the microalgae which exist already in the commercial market are Spirulina, Chlorella, Haematococcus and Chaetoceros. Because of this, industrial microalga is a field that needs to be exploited primarily to produce promising high-valued chemicals for nutraceuticals, functional food and living feed and other feed additives. Additionally, these creatures were visualized as the “food for the future” because of the many applications that it possess. Historically, the first microalgae to be commercialized for food industry was the Nostoc species over many decades and consumed in China, Taiwan, Japan and other Southeast Asian Nations. Briefly, Nostoc species is a blue-green alga and sometimes called freshwater grapes which are in a jelly-like ball surrounded by thick mucilage. Thus, this review article aims to present the background antecedents of how phytoplankton discovered and existed in the Philippines for many decades and to discuss various phytoplankton with their biological components necessary for agriculture, fisheries, industrial, pharmaceutical, medical and other fields of endeavor.
Keywords: Biological; Chemical; Constituents; History; Minute